IMPLEMENTASI PERATURAN DAERAH NOMOR 11 TAHUN 2013 TENTANG PENGELOLAAN SAMPAH DI KOTA BATAM - Putri Andini, Liza; Lubna salsabila (SCIENTIA JOURNAL, 2022)
Policy implementation refers to the stage after a policy is developed and must be implemented. The government and the community must work together to get the best results, namely in the process of transporting, sorting, and managing waste in the community. The purpose of this study is to identify each step in implementing the policy of Regional Regulation No. 11 of 2013 concerning waste management in Batam City, in order to reduce waste pollution. The researcher uses descriptive research method with a qualitative approach and qualitative analysis methods in his research. This research was conducted with the assistance of the Environment Agency, cleaning staff, and community members involved in the waste management process. The process of socialization and education related to good waste management through waste banks and non-governmental organizations that have not been maximized, the strength of the Regional Revenue and Expenditure Budget (APBD) is lacking, and public awareness of clean living is the reason it still exists. problem in this case. Researchers assess that the current government policy program has been running well, but is still not ideal, and needs to be evaluated periodically. Keywords: Implementation; Waste Management; Cleanliness.